Análisis del procedimiento de detención de los implicados en delitos penales en el Ecuador. - Llumiguano Trujillo, Rosa Judith (2024)
The main objective of the investigation is to analyze the detention procedure of those involved in criminal offenses in Ecuador to demonstrate the various elements that comprise it and possible weaknesses. For this, it established the Ecuadorian legal parameters regarding the detention procedure of those involved in criminal offenses in Ecuador, through the study of the norm defining the margins of action for compliance with them. He exposed the levels of compliance in relation to the norm regarding the detention procedure of those involved in criminal offenses, with the study of criminal cases executed and duly documented in the country, and compared the true compliance with the detention procedures of those involved in criminal offenses. criminal offenses in Ecuador evidencing the consequences. Based on qualitative bibliographic research, collecting information by reviewing existing records included in texts, Ecuadorian laws related to the subject of study and case files in which illegal detection is a relevant topic. Therefore, it was possible to determine the existence of a clearly defined legal structure and in accordance with human rights, however, with the study carried out, the erroneous practice was evidenced by the officials who are in charge of this function, in this sense, It is recommended to socialize this type of information so that citizens have sufficient knowledge to protect rights in the event of an evident violation, thus preventing social, physical and psychological affectation and even disappearances without response from the Ecuadorian State. Keywords: procedure, detention, citizens, human rights.